Trends in dental caries in Indian children for the past 25 years - Abhishek Mehta (Wolters Kluwer Medknow Publications, 2018)
Background: The economic liberalization which was started 25 years back in India has led to a rising gross domestic product and per capita income and a decline in poverty. There has been an improvement in various health status indicators in the Indian population. As oral health is an integral part of general health, a retrospective study was designed to assess the effect of economic liberalization on dental caries experience in Indian children. Materials and Methods: A systematic literature search was conducted to find studies done on dental caries prevalence in children in India from the year 1992-2016. Mesh and free text terms "child," "dental caries," and "India" were searched in databases - PubMed and PubMed Central. A total of 1468 titles were screened, out of which 191 articles were shortlisted for further inspection. Finally, 69 studies were found suitable for final analysis. Results: The pooled caries prevalence was between 50.84% and 62.41% at 5-year interval. There was a decline in caries prevalence in 2-5 and 11-15 years of age group. The overall weighed mean of 2.4, 2.7, and 1.9 was observed in three different age groups. Significant caries index (SiC) of more than 3 was observed in all the age groups. Conclusion: The present review suggests that more than half of Indian children have been affected by dental caries. High SIC index score suggests a skewed distribution of caries among Indian children. This data may aid in planning further exploratory research and oral health care services for children by the stakeholders.